Molecular Detection of Antibiotic Resistance Genes Using Respiratory Sample from Pneumonia Patients - Eman Abdullah Alsuof; Ahmad R. Alsayed; Manar Saleh Zraikat; Heba A. Khader; Luai Z. Hasoun; Mamoon Zihlif; Osama Abu Ata; Malek A. Zihlif; Mahmoud Abu-Samak; Mohammed Al Maqbali (Antibiotics)
Introduction/Objectives: Antibiotic resistance makes the treatment of pneumonia challenging. Effective management depends on accurate diagnostic techniques to identify resistance genes and customize drugs. This study primarily aimed to identify antibiotic resistance genes in respiratory samples from patients with pneumonia using polymerase chain reaction (PCR) to determine the prevalence of specific resistance genes and analyze clinical factors contributing to antibiotic resistance, as well as to provide actionable insights into resistance patterns in Jordan and support efforts to improve pneumonia management. Methods: This retrospective observational study included 114 patients who were diagnosed with pneumonia. Clinical data, including prior antibiotic exposure and treatment history, were collected. PCR diagnostics were used to detect resistance genes in respiratory samples. In this study, we evaluated 14 antibiotic resistance genes in pneumonia pathogens, highlighting their diverse resistance mechanisms. Results: Mec A was the most frequently detected gene, appearing in 87 samples (77.3%). Additionally, Tem in 80 samples (70.2%), Oxa-48-like in 15 samples (13.2%), and Ctx-M-1 in 38 samples (33.3%) were among the most commonly detected genes. In contrast, Oxa-40-like (7.0%), Vim (8.8%), and Imp (4.4%) genes exhibited a lower prevalence. The Oxa-51-like gene showed the only significant association with ertapenem resistance (p-value = 0.046). Further analysis revealed statistically significant associations between Mec A and methicillin resistance (p < 0.001), underscoring its critical role. However, other genes, such as Oxa-40-like and Oxa-48-like, showed no significant correlation with the antibiotic resistance patterns of imipenem and meropenem (p > 0.05). Conclusions: This study demonstrates the utility of PCR-based diagnostics for detecting resistance genes and highlights the critical clinical factors associated with antibiotic resistance in patients with pneumonia. These findings underscore the importance of integrating molecular diagnostics into routine care to improve treatment outcomes and combat the growing threat of antibiotic resistance in Jordan. This highlights PCR’s value in guiding effective treatment strategies and addressing multidrug-resistant pneumonia.